The morphodynamic response of a gravel barrier to unimodal and bimodal storm wave conditions - KRISTIAN IONS (Frontiers in Marine Science, 2023)
Gravel barrier beaches can offer natural protection to coastlines from adversestorm conditions. Understanding the morphodynamics of gravel barrier beachesis vital for the effective and sustainable management of these systems. Here, weuse a synthetic dataset to investigate the morphodynamic response of the gravelbarrier beach at Hurst Castle Spit, located on the Southwest coast of the UnitedKingdom, to both unimodal and bimodal storms. This spit is exposed to wind andswell waves propagating up the English Channel from the Southwest approachesand has suffered repeated storm erosion. The results are analyzed to identify thekey drivers that govern the spatio-temporal gravel barrier morphodynamicresponses to storms and to explore the morphodynamic states of the barrier.We found that the morphodynamic response of the barrier beach is stronglyinfluenced by the combination of storm wave height and still water level. Further,the presence of swell waves can be a controlling factor in the barrier response.